Interest of rural youth of Medak district, Telangana, India towards the skill course of medical laboratory technician - Adepu Sai Sindhu; Nomula Raavi Varma; Lalichetti Sagar; Metuku Devender Reddy (International Journal Of Community Medicine And Public Health, 2026)
Background: India’s rapidly expanding healthcare diagnostics sector faces a critical shortage of qualified medical laboratory professionals, yet the Diploma in Medical Laboratory Technology (DMLT) remains poorly recognized among science students who could benefit most. This study assessed DMLT awareness, career preferences, and enrolment-influencing factors among intermediate Bi.P.C students in rural Medak District, Telangana. Methods: A cross-sectional survey using a validated questionnaire was administered to 486 Bi.P.C students from eight colleges in Medak District. The instrument covered demographics, academic interests, DMLT awareness, laboratory experience, career goals, and enrolment intent (response rate: 100%). Data were analyzed using descriptive statistics, chi-square tests, logistic regression, and a Random Forest classifier (p < 0.05). Results: Only 38% of students had heard of DMLT; 30% had no knowledge and 20% showed no interest despite being aware. Although 93% expressed interest in medical science, nursing (83%), laboratory technology (62%), and pharmacy (31%) dominated career preferences. Prior laboratory experience was significantly associated with DMLT interest (p < 0.05). Long-term career goals (β = +1.8), Bi.P.C subject preference (β = +1.6), and career counselling (β = +0.8) were the strongest positive predictors; parental influence was negligible (β = −0.4). Random Forest classification achieved 83.7% accuracy (F1 = 0.84), with DMLT knowledge and lab experience as top features. Conclusions: The principal barrier to DMLT enrolment is informational rather than motivational. Structured awareness sessions, laboratory demonstrations, and periodic career counselling are recommended to convert existing medical science interest into DMLT-specific enrolment among rural youth.